Selective Solid Phase Extraction and Preconcentration of Ultra Trace Molybdenum Using Modified C18 Membrane Disks - Reza Ghiasvand, Ali; Mohagheghzadeh, Elham (Asian Journal of Chemistry, 2016)
A simple and reliable method for the selective extraction of ultra trace Mo(VI) ions using octadecyl-bonded silica membrane disks modified by a-benzoinoxime and spectrophotometric determination with thiocyanate was developed. The influences of the sample matrix amount of the extractant and type and minimum amount of the eluent and flow rates on the extraction efficiency were evaluated. Most of the cations examined have no interfering effect on the extraction and determination of molybdenum. However, effects of some interfering species such as Cu(II), Hg(II), Ce(IV) and Zr(IV) were decreased or eliminated in the presence of EDTA or rinsing of the membrane disk prior to the elution of the complex. The limit of detection of the proposed method is 0.08 ng/mL. The maximal capacity of the membrane disks modified with 40 mg of a-benzoinoxime was found to be 329 ± 43 μg of molybdenum. The method was applied to the extraction and determination of molybdenum in natural waters, lucerne and spinach.